Assessing the Impact of Opioid Analgesics on Pain Intensity Among Breast Cancer Inpatients at Dharmais Cancer Hospital, Jakarta - Annisa Farida Muti; Salsabila Azka Maharan Azka Maharani; Dhigna Luthfiyani Citra Pradana Pradana; Eldiza Puji Rahmi (LPPM Akafarma Sunan Giri Ponorogo, 2026)
Pain is a significant primary complaint among breast cancer patients. The WHO Analgesic Ladder guidelines recommend the use of opioid analgesics as a primary management strategy for cancer pain. However, a periodic evaluation of its effectiveness in specific populations remains necessary. This study aimed to evaluate the effectiveness of opioid analgesic therapy in reducing pain intensity for breast cancer inpatients at Dharmais Cancer Hospital, Jakarta, in 2023. This research was an observational study with a retrospective design. The study sample comprised 58 medical records from breast cancer inpatients who had received opioid analgesic therapy, collected using a total sampling technique. Data analysis was performed using the non-parametric Wilcoxon signed-rank test to compare pain intensity before and after the administration of therapy. The results of the statistical analysis demonstrated a highly significant reduction in pain scores following the administration of opioid analgesic therapy (p < 0.001). The administration of opioid analgesics were significantly effective in the management of pain for breast cancer patients at Dharmais Cancer Hospital, Jakarta.